A randomized controlled trial of the effects of dog-assisted versus robot dog-assisted therapy for children with autism or Down syndrome - Steffie Van Der Steen; Erica Kamphorst; Richard E. Griffioen (PLoS ONE, 2025)
Research with controlled or crossover designs in animal-assisted therapy have largely used control groups receiving no treatment or treatment as usual, which can potentially inflate the effects of these interventions. It is therefore not always clear whether this type of therapy has a positive effect on, for example, the social skills of children with special support needs. To address this, the current study compared children (7-16 years, n =  65) with autism or Down syndrome who received five sessions of dog-assisted therapy (n =  24; 9 female) with an active control group who received five similar sessions of robot dog-assisted therapy (n =  21; 8 female) and a no-treatment control group (n =  20; 8 female). The robot dog was capable of performing autonomous behavior and responding to the child’s actions and verbalizations. Using parental questionnaires, we assessed children’s social and emotional skills before and after the therapy sessions or waiting period and included a follow-up measurement after 4-6 weeks. On a group level, multilevel analyses showed that children who received dog-assisted therapy improved significantly more in terms of emotional attunement and emotion regulation than children in the two other conditions. No significant differences were found for social confidence, conversational attunement, social cognition, and social motivation. Change from post-test to follow-up was also less apparent. Yet, on a more individual level, when looking at the Reliable Change Index (RCI), most of the highest RCIs (within the 90th percentile) were found in the dog-assisted therapy group. In contrast, most of the lowest RCIs (within the 10th percentile) were found in the robot-assisted group. We discuss the pros and cons of a more individualized approach in this field of study and propose a possible alternative by focusing on interaction dynamics.